SEWAGE SLUDGE VALORIZATION: BIOCHAR PRODUCTION FOR ENHANCED ADSORPTION OF CONTAMINANTS - Agoe, Andy Kofi (Nazarbayev University Graduate School of Engineering and Digital Science, 2024)
Municipal sewage sludge (SS) from wastewater treatment has attracted much interest from the agriculture and energy sectors. However, concerns about harmful contaminants in sewage sludge limit its direct use in developed countries. Alternatively, a thermochemical conversion process such as pyrolysis of SS produces several value-added products, including bio-oil and a stabilized form of pyrolytic residuals with a large specific surface area and functional groups. This study examined the effects of pyrolysis temperature (500 oC, 650 oC, and 850 oC) and SS particle size (S1: 800 - 1000 µm, S2: 400 - 800 µm, S3: 100 - 400 µm, S4: ≤ 100 µm) on the derived biochar’s yield and its methylene blue and mercury adsorption capacity. The adsorption capacity and kinetics results were used to identify the best thermal treatment conditions for the SS. Irrespective of the particle size at a pyrolysis temperature of 500 oC, the SS-derived biochar followed the second-order adsorption kinetics. SS-derived biochar of 100 - 400 µm particle size was identified as a promising adsorbent due to its high adsorption capacity for methylene blue and a comparable initial adsorption and desorption rate constant based on the Elovich model. Further alkali treatment (Biochar: NaOH = 3:4) of 100 - 400 µm particle size enhanced the specific surface area of the biochar from 27.5 m2/g to 144.27 m2/g and increased the adsorption capacity of methylene blue and mercury to 35 mg/g and 36 mg/g respectively. These SS-based adsorbents are cost-effective and have a very high methylene blue and mercury adsorption capacity, serving as a beneficial modifier adsorbent. This advantage is poised to refine parameters in sewage sludge preparation before and after pyrolysis, offering a dependable material for engineering applications.
Keywords: type of access: embargo; Municipal sewage sludge; Pyrolysis; Adsorption; Biochar; Methylene blue; Mercury